Partner Contributions to Goal Pursuit: Findings From Repeated Daily Life Assessments With Older Couples. (27th March 2021) - Zambrano, Elizabeth; Pauly, Theresa; Gerstorf, Denis; Ashe, Maureen C; Madden, Kenneth M; Hoppmann, Christiane A
Abstract: Objectives: This study focuses on the role of spouses for facilitating goal progress during a phase in life when individual resources for goal pursuit are particularly limited. Specifically, we examined the moderating role of relationship characteristics in old age for time-varying partner involvement–goal progress associations as couples engaged in their everyday lives. We also assessed time-varying associations between everyday goal progress, effectiveness of partner contributions, and spousal satisfaction with this contribution. Methods: We used multilevel modeling to analyze data from 118 couples ( M age = 70 years, SD = 5.9; 60–87 years, 50% women; 57% White). Both partners reported their personal goals and provided information on relationship satisfaction, conflict, and support. They also provided simultaneous ratings of everyday goal progress, effort, partner involvement as well as effectiveness of and satisfaction with partner contribution up to three times daily over 7 days. Results: In line with expectations, higher relationship satisfaction and support and lower conflict were associated with higher goal progress when the partner was involved in goal pursuit. Both effectiveness of and satisfaction with partner contributions were positively associated with everyday goal progress. Discussion: Whether partner involvement is beneficial for goal progress depends on characteristics of the relationship as well as what partners actually do in everyday life. This highlights the importance of considering both stable person characteristics as well as time-varying processes to capture the complexity of goal pursuit in older couples.